MODEL PENGELOLAAN PENDAYAGUNAAN SUMBER DAYA AIR PADA USAHA AIR MINUM DALAM KEMASAN (AMDK) DI INDONESIA - Ajeng Famela; Achmad jaka Santos Adiwijaya; Agus Surachman (JURNAL ILMIAH LIVING LAW, 2020)
Liquid water is a physiological physiologic where humans need air to retain their lives, the existence of article 33 Constitution 1945 as a corridor of air resource management, where the utilization of permissible is done constitutionally and aims to the maximum for prosperity of people. The method of approach used in this study is normative juridical, which is the law conceptualized as norm, rule, principle or dogma. Data collection techniques used through literature research methods and Interviews as well as using qualitative analysis. ased on the research conducted by the authors that the management of water resources utilization pursuant to article 33 of the Constitution of 1945 is the existence of state rights over water that can be said to exist when the state, which by the constitution 1945 is mandated to create a policy (beleid), still in control in carrying out the management action (bestuurdaad), the action of the arrangement (regelendaad), management actions (beheersdaad) and supervision measures  (toezichthoudensdaad) as the development of the model of water resource utilization management on the business of bottled drinking water Government can develop models from licensing, the addition of administrative sanki, expansion of bottled water production, and initiating private cooperation with the government through the form of BOT agreements